2018
DOI: 10.2323/jgam.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of multi-drug resistant <i>Escherichia coli</i> isolates from tropical environments in Southeast Asia

Abstract: The emergence of antibiotic resistance among multidrug-resistant (MDR) microbes is of growing concern, and threatens public health globally. A total of 129 Escherichia coli isolates were recovered from lowland aqueous environments near hospitals and medical service centers in the vicinity of Kuala Lumpur, Malaysia. Among the eleven antibacterial agents tested, the isolates were highly resistant to trimethoprim-sulfamethoxazole (83.7%) and nalidixic acid (71.3%) and moderately resistant to ampicillin and chlora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Therefore, we can say that the results obtained in the present study are in line with those of (Martin et al, 2021). Several studies have shown the presence of antibiotic resistance genes in hospital effluents (Hara et al, 2018;Paul et al, 2018;Yousfi et al, 2019;Fadare and Okoh, 2021), but very few have focused on the presence of HMRGs in effluents. This study provides new scientific data on the presence of heavy metals in hospital effluents.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we can say that the results obtained in the present study are in line with those of (Martin et al, 2021). Several studies have shown the presence of antibiotic resistance genes in hospital effluents (Hara et al, 2018;Paul et al, 2018;Yousfi et al, 2019;Fadare and Okoh, 2021), but very few have focused on the presence of HMRGs in effluents. This study provides new scientific data on the presence of heavy metals in hospital effluents.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the antibiotic susceptibility testing are presented in Table 2. Thus, our results are similar to an earlier study which also reported that E. coli isolated from waterbodies of Malaysia exhibited lower levels of resistance for aminoglycosides [43]. However, another study from India reported that E. coli strains isolated from coastal waters of India were highly resistant for streptomycin and gentamicin [44].…”
Section: Aminoglycoside Susceptibilities and Plasmid-mediated Aminogl...supporting
confidence: 91%
“…Selective pressure from the environment may cause these bacteria to acquire resistance genes and serve as a significant reservoir for the transmission of antimicrobial resistance (AMR) determinants, becoming a threat to global health ( 4 6 ). Here, we sequenced three E. coli strains that were isolated from river water as reported previously ( 7 ) to determine their responsible AMR determinants. River water receiving treated and untreated wastewater discharged from nearby hospitals and medical service centers was collected from the Gombak River (3°10′13.2″N, 101°41′41.6″E) in Kuala Lumpur, Malaysia.…”
Section: Announcementmentioning
confidence: 99%
“…The multidrug-resistant (MDR) strains were then obtained by disk diffusion assay ( 10 ). The MDR E. coli strains GR2, GR3, and GR5 ( 7 ) were selected for whole-genome sequencing. Genomic DNA was extracted from overnight cultures grown on Luria-Bertani (LB) plates using an ISOIL for Beads Beating kit (Nippon Gene) following the manufacturer’s protocol, with modification of the centrifugation speed and time to 12,000 rpm for 10 min.…”
Section: Announcementmentioning
confidence: 99%